Evaluation of performance of the inspection teams in the appraisal of health situation in Dhi-Qar case research in the Health Department of Dhi-Qar - جبار, مشعل زوري (Journal of Economics and Administrative Sciences, 2019)
AbstractResearch aims : The aim of the research is to evaluate the reality of the inspection teams' work in the health institutions belonging to Dhi-Qar health office .Purpose: This research seeks to present a point of view based on knowing the extent of health service quality in Dhi-Qar governorate and discover the role of the inspection teams in enhancing the health service. Design / Methodology/ Approach: The experimental method has been used and the questionnaire has also been used to collect data in order to develop a reliable and correct measurement model for the research's variables . The research's hypotheses have been tested through using some statistical treatments. Findings: The research has led to the enhancement and development of health reality in Dhi-Qar governorate and to the enhancement of its health service quality . That has been reflected by an increase in the numbers of patients who come to all hospitals for checking in general . Practical Affects : This research provides a useful benchmark for quality health service and helps managers to use it to assess the current state of hospital performance Originality / Value : This research pledges to help those who offer health service , to deal with the challenge represented by the increase in the numbers of patients who go to  hospitals and to show how effective the inspection teams are in the performance of hospitals